The optimal gestation for pertussis vaccination during pregnancy: a prospective cohort study - Naidu, Madison A.; Muljadi, Ruth; Davies-Tuck, Miranda L.; Wallace, Euan M.; Giles, Michelle L. (American journal of obstetrics and gynecology, 2016)
There is an increasing incidence of pertussis infection in infants too young to be adequately protected via vaccination. Maternal pertussis vaccination during the third trimester of pregnancy is a new strategy to provide protection to newborn infants. This study sought to determine the optimal gestational window for vaccination in the third trimester. This prospective study recruited 3 groups of women: an early vaccination group, vaccinated between 28-32 weeks’ gestation; a late vaccination group, vaccinated between 33-36 weeks’ gestation; and an unvaccinated control group. Maternal venous blood was taken prior to pertussis vaccination. At birth, infant cord blood was collected to determine antibody levels to pertussis toxin (PT), pertactin (PRN), and filamentous hemagglutinin (FHA). In all, 154 women were recruited from April through September 2014. There was no significant difference between maternal PRN and FHA antibody levels among the 3 groups, however, PT was higher in the early compared to late vaccination group (P = .05). Cord blood antibody levels to PT, PRN, and FHA were significantly higher in those born to vaccinated women compared with unvaccinated controls (P < .001, P = .001, and P < .001, respectively). Vaccination between 28-32 weeks’ gestation resulted in significantly higher cord blood PT (4.18.0 vs 3.50 IU/mL, P = .009), PRN (5.83 vs 5.31 IU/mL, P = .03), and FHA (5.56 vs 5.03 IU/mL, P = .03) antibody levels than vaccination between 33-36 weeks’ gestation. When adjusted for maternal prevaccination antibody levels, PT levels in early vs late vaccination approached significance (P = .06). PRN levels were significantly higher in the early vaccination group (P = .003). There was no significant difference for FHA antibody levels between the 2 groups (P = .16). Maternal vaccination during the third trimester is effective in affording higher levels of pertussis antibody protection to the newborn infant. Vaccination early in the third trimester appears more effective than later in pregnancy.